Program Pendidikan Karakter Religius Siswa SMP Dharma Utama untuk Mewujudkan Remaja Smart di Desa Sukasari - Nissa Zahru Oktavianti; Rahimah Rahimah (Institut Teknologi dan Bisnis Semarang, 2024)
This research aims to analyze the implementation of the Religious Character Education Program at Dharma Utama Middle School as an effort to form SMART (Spiritual, Capable, Adaptive, Responsive and Responsible) teenagers in Sukasari Village. Thus, religious character education at Dharma Utama Middle School does not only focus on academic aspects, but also on forming a balanced character, thereby creating teenagers who have integrity and are ready to face the future. It is hoped that this research can become a reference for other educational institutions in developing similar programs to improve the quality of character education at the secondary school level.